Scaling dermatitis of the scalp. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
This title refers to a dermatitis caused by a torpid inflammation of the scalp with normal hair. Its prominent sign consists of scaling at the level of hair junction to the scalp. The differential diagnosis of these lesions is rather difficult due to both the presence of hair and the physiological characteristics of the scalp. The former makes the observation of the lesions more difficult. The latter give a common mark to diseases which in other sites are much more different to each other. (...).